CEO characteristics and earnings management: evidence from Indonesia - Ameila Ameila; Rizky Eriandani (Journal of Management and Business, 2021)
The CEO has an important role as a decision maker in the company and is responsible for the company's performance. This study was conducted to measure the effect of CEO on earnings management in 495 samples of non-financial companies listed on the Indonesia Stock Exchange in 2017-2019 using panel regression analysis with classical assumption testing. The results of panel regression examiners show that there is no significant effect between female CEOs and CEO turnover on earnings management proxies with discretionary accruals. Meanwhile, CEO tenure and company size show a significant negative relationship with earnings management. On the other hand, leverage and return on assets have a significant positive effect on earnings management. In addition, there is no significant influence between company age and Market to Book ratio on earnings management.